2003
DOI: 10.1076/opep.10.4.259.15908
|View full text |Cite
|
Sign up to set email alerts
|

LOCS III examination at the slit lamp, do settings matter?

Abstract: For nuclear opacity and nuclear colour measurements, changing settings between examinations increases variability without evidence of systematic bias. However, using a thicker slit beam induced a systematic bias. For cortical and posterior subcapsular lens opacity, varying the illumination had more marked effects on reproducibility without a systematic bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…ASOCT imaging is simple to perform and rapid, and has a low learning curve. This is in contrast to slit-lamp-based photographic grading systems in which slit-lamp settings may influence the grading scores, and more practice and training are required to achieve optimum consistency in lens grading 11. The ordinal scale in the LOCS III grading systems may also be inadequate for detecting small changes in longitudinal studies.…”
Section: Discussionmentioning
confidence: 98%
“…ASOCT imaging is simple to perform and rapid, and has a low learning curve. This is in contrast to slit-lamp-based photographic grading systems in which slit-lamp settings may influence the grading scores, and more practice and training are required to achieve optimum consistency in lens grading 11. The ordinal scale in the LOCS III grading systems may also be inadequate for detecting small changes in longitudinal studies.…”
Section: Discussionmentioning
confidence: 98%
“…Cortical and posterior subcapsular grading was done with a 5V setting, no filter, a 3.0 to 4.0 mm slit height, 3-to 5-degree variable angle slit width, and focus on the plane of the pupil for C and on the posterior capsule for PSC. 8 The percentage agreement and k values of the grades of the 3 observers were calculated and compared. The k and agreement values before standardization of the system and after standardization were compared.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that using the same slitlamp, constant illumination, a fixed slit width, and no neutral filter improves inter-observer agreement. 8 This study evaluated whether there was significant inter-observer agreement between observers at different levels of training and whether inter-observer agreement improved after discussion and standardization of the LOCS III scale.…”
mentioning
confidence: 99%
“…The most frequently used is the Lens Opacity Classification System version III (LOCSIII; Chylack et al 1993) and Wisconsin Cataract Grading System (WCGS; Panchapakesan et al 1997). These systems are based on retro-illumination and slit-lamp images and rely on subjective data, depending on the examination settings and examiner's expertise (Gao et al 2013;Kirwan et al 2003). In this work, it was shown that SVM can be a useful tool for the automatic classification of the cataract severity, based on the ultrasound technique.…”
Section: P-valuementioning
confidence: 99%